Pengembangan Media Pembelajaran ICT untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa Kelas VII SMPN 2 Wewewa Tengah - Tanggu, Daud; Napu, Timotius Woda; Lede, Yulius Keremata; Making, Samuel Rex Mulyadi (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study is to improve students' problem-solving abilities related to the concept of fractions by using ICT learning media. This study uses a type of research, namely design research, researchers also use qualitative descriptive analysis to analyze students' problem-solving abilities. The subjects in this study were seventh-grade students at SMP Negeri 2 Wewewa Tengah, in the 2024/2025 academic year and the object of the study was the development of ICT learning media to improve the problem-solving abilities of seventh-grade students of SMP Negeri 2 Wewewa Tengah. The instruments used in this study were learning observations, test questions, interviews. Data collection techniques in this study were by providing test questions, learning observations, interviews, and documentation. Based on the results of the research and data analysis carried out, it can be concluded that students' problem-solving abilities based on the Polya indicators of seventh-grade students of SMP Negeri 2 Wewewa Tengah. The ability of students in the High category increased from 0% to 15%, the ability of students in the medium category also increased from only 5% to 80%, while in the low category decreased from 95% to only 5%. This means that using ICT learning media with phET as a teaching medium can help students improve their problem-solving skills in fraction operations.